2018
DOI: 10.32400/gc.13.04.21018.2018
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Penerapan Sistem Transaksi Non Tunai Dalam Pengelolaan Keuangan Daerah Pada Dinas Lingkungan Hidup Kota Bitung

Abstract: In an effort to improve an efficient regional financial management system, the government issued the Minister of Home Affairs Circular No. 910/1866 / SJ concerning the Implementation of Non-Cash Transactions on April 17, 2017, which is in accordance with the Provisions of Article 283 paragraph (2) of Act Number 23 of 2014 and in accordance with Presidential Instruction Number 10 of 2016 concerning Prevention and Eradication of Corruption. Non-cash transactions are transactions that do not make payments in cash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
1
1
0
9
Order By: Relevance
“…Based on the results of the interview above, it can be concluded that the non-cash payment system mostly provides benefits for MSMEs in their records, especially in terms of sales transactions. The results of this study are supported by research by Pelealu et al [15], that non-cash transactions are more efficient because money is more controlled and can improve financial management control.…”
Section: B Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Based on the results of the interview above, it can be concluded that the non-cash payment system mostly provides benefits for MSMEs in their records, especially in terms of sales transactions. The results of this study are supported by research by Pelealu et al [15], that non-cash transactions are more efficient because money is more controlled and can improve financial management control.…”
Section: B Discussionsupporting
confidence: 81%
“…910/1867/SJ regarding the implementation of non-cash transactions at regional governments. The implementation of Non-Cash Transactions is an effort of the government in improving regional financial management, this is in accordance with the provisions of Article 283 paragraph (2) of Undangundang Nomor 23 Tahun 2014 [14] concerning Regional Government, which mandates that regional financial management be carried out in an orderly manner, obeying the laws and regulations, efficient, economically effective, transparent and responsible by paying attention to a sense of justice, propriety, and benefits to society [15].…”
Section: E Non-cash Payment Systemmentioning
confidence: 99%
“…Penelitian ini juga sesuai dengan penelitian yang dilakukan oleh Pelealu (2018), tentang faktor penghambat implementasi kebijakan sistem transaksi non tunai dalam pengelolaan keuangan daerah yaitu proses administrasi yang terkadang terhambat, sosialisasi proses, penerapannya hingga penerimaan retribusi dengan nilai nominal kecil. Pada penerapan sistem non tunai ini, didapati hasil bahwa Pemerintah Daerah mengalami hambatan dalam pelaksanaannya.…”
Section: Faktor-faktor Yang Menjadi Hambatan Dalam Implementasi Kebij...unclassified
“…Transaksi non-tunai merupakan salah satu kegiatan pemindahbukuan nominal dana tertentu yang bersumber dari satu instansi ke instansi yang lain dengan menggunakan cek sebagai bukti transaksi, uang elektronik, bilyet, giro dan penggunaan alat pembayaran lain atau sejenisnya. Adapun Pihak yanag berperan sebagai pembayar transaksi non -tunai yaitu Kepala Organisasi Pemerintah Daerah (OPD), Bendahara Penerimaan Pembantu dan Bendahara Pengeluaran Pembantu (Pelealu et al, 2018). Pada penelitian (Hendrawan et al, 2019) mengungkapkan bahwa suatu wujud mengimplementasikan transaksi non-tunai pada pemerintahan daerah merupakan upaya untuk meraih pengelolaan keuangan yang bersifat transparency dan accountability.…”
Section: Pendahuluanunclassified